Challenges in diagnosis and management of giant solitary fibrous tumour of pleura: a case report. Issue 1 (December 2016) - Tan, Jessica; Hsu, Anne
Abstract Background Majority of patients with solitary fibrous tumours of the pleura (SFTP) are asymptomatic. Acute presentation with symptoms resulting from mass effect due to rapid expansion of tumour size has not been reported before. Case presentation This report chronicles the case of a giant SFTP in a 76-year-old lady who presented with acute onset of haemoptysis, left-sided pleuritic chest pain and hoarseness of voice. Her chest radiograph showed a large left upper hemithorax mass with an ipsilateral effusion. Computed tomography (CT) scan of the thorax confirmed the presence of a pleural-based mass lesion in the left apex measuring 9.7 cm with close apposition to the aortic arch. The mass demonstrated neovascularization and there was also presence of a moderate-sized heterogeneous-appearing left pleural effusion. Thoracocentesis yielded deeply haemoserous pleural fluid with a pleural aspirate hematocrit closely approaching that of peripheral blood hematocrit and alongside a 2 unit decrease in haemoglobin, was indicative of a haemothorax. Repeat CT 10 days from initial presentation showed reduction in size of the left apical mass as well as resolution of the left effusion. This was consistent with the occurrence of an intra-tumoural bleed resulting in rapid increase in the size of the SFTP, causing rupture of superficial blood vessels on the tumour surface (haemothorax) and consequential compression of the lung parenchyma (haemoptysis) and left recurrent laryngeal nerve (hoarseness of voice). The patient eventually underwent an uneventful surgical resection. Conclusion A benign SFTP can present acutely with compressive symptoms as a result of spontaneous intra-tumoural bleed causing sudden increase in its size. It is important to allow temporal regression of these acute changes before deciding on surgical resectability.